Real-time observation of meso-fracture process in backfill body during mine subsidence using X-ray CT under uniaxial compressive conditions. (15th June 2016) - Sun, Wei; Wu, Aixiang; Hou, Kepeng; Yang, Yi; Liu, Lei; Wen, Yiming
Graphical abstract: Highlights: When the backfill body is subjected to external load, cracks extend from the tensile stress concentration region around the hole. Increasing the amount of waste rock increases the CT value, decreases the SD value, and enlarges the high-density region in the CT image. The UCS of the backfill body decreases if the amount of waste rock exceeds 30%. Increasing the amount of waste rock increases the UCS of the backfill body and then decreases it with the addition of the same amount of cement. Abstract: Surface subsidence and severe damage by solid wastes are major environmental disasters in mining. The integrated treatment of surface subsidence and solid wastes can be realized through the preparation of solid wastes into paste for backfilling subsidence areas. The mechanical properties of backfill bodies are the key to a successful backfilling. This study investigates the conditions of meso-scale failure in the backfill body in a subsidence area under uniaxial compressive strength (UCS) conditions by adopting computed tomography (CT) scanning when the waste rock contents are 10%, 30%, and 50% and the cement dosages are 1% and 2%. A large number of primary multi-scale defective structures internally evolve in the backfill body in the initial state. These structures are mainly pore structures. Moreover, crack initiation and expansion occur in the area with concentrated tensile stress on the periphery of the pore space when the backfill body is subjected to external load. This effect persists until the backfill body fails. Along with an increase in waste rock content, the CT value of the backfill body correspondingly increases, the standard deviation (SD) of the CT value decreases, and the number of high-density areas in the CT images increases. When the waste rock content is more than 30%, the UCS of the backfill body declines. With an increase in cement content, the plastic deformation of the backfill body decreases, and obvious through cracks appear under a peak intensity of 80%. Under identical cement dosages, the UCS of the backfill body shows an upward to downward trend along with an increase in waste rock content. The meso-structure of the backfill body when the waste rock content is 30% is more reasonable than that of the backfill body under a different ratio and thus shows better mechanical properties.